THE POTENTIAL ANTIPYRETIC ACTIVITY OF FICUS SEPTICA LEAF EXTRACT IN ICR MICE - Rodaje, Marife D.; Yaun, Emma A.; Sacramento, Serene Desiree B.; Ybañez, Adrian P.; Ybañez, Rochelle Haidee D. (Journal of Agriculture and Technology Management; Journal of Agriculture and Technology Management (JATM) Volume 19 Issue 1, January-June 2016, 2016)
Ficus septica is a tree or shrub that is endemic in the Philippines. In this study, the potential antipyretic activity of the ethanol leaf extract of F. septica was evaluated. Initially, qualitative phytochemical screening was performed to evaluate the presence of active constituents in the extract. In the experiment, a total of 21 ICR mice was used [divided into three equal groups: negative (distilled water), positive (Paracetamol) and experimental ( F. septica )] and pyrexia was induced using yeast. F. septica extract and Paracetamol were given at a dose of 150 mg/kg. Animals were acclimatized for seven days. Prior to induction of pyrexia, basal body temperature was obtained. After induction, corresponding treatments were given and the body temperature was monitored hourly for 5 times.  Data were analysed using one-way analysis of variance (ANOVA). Results revealed that F. septica extract had a significant anti-pyretic activity similar to paracetamol at the onset of action on the first hour and the third hour (p >0.05). A mean reduction of temperature of 0.3 centigrade was observed.  The present study showed that the F. septica extract had a potential anti-pyretic effect. Further studies must be made on the varying doses and toxicity of the T. septica extract.